The Mud and the Mirth : Marine Cartoonists in World War I - Scott, Cord A. (Book collections on Project MUSE., 2022)
"Visual arts constitute a significant portion of the Marines' life, from training manuals to public appearances. Illustrations may inform, educate, or entertain the masses, be they civilians or military personnel. The Mud and the Mirth takes a deeper look at comic illustrations from the earliest publications for the Marine Corps-the Recruiters Bulletin, the Marines Magazine, and the Marines Bulletin-prior to World War I, as well as presents the entire collection of Stars and Stripes cartoons illustrated by Marine cartoonist Abian A. Wallgren"--